2018
DOI: 10.1097/phm.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Onabotulinum Toxin A Injections Into the Salivary Glands for Spinal Muscle Atrophy Type I

Abstract: Ultrasound guided BTX-A injections to the salivary glands may be a safe and effective method of decreasing drooling in patients with SMA I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Of the 31 total studies, 15 studies evaluated drooling in children with cerebral palsy specifically or combination with an unspecified intellectual disability, 7 , 13 , 16 - 28 14 studies evaluated drooling in patients with a variety of neurologic or neurodevelopmental impairments, 10 , 14 , 29 - 40 1 study looked at hypersalivation in spinal muscle atrophy type I, 41 and 1 study involved a case series with Rett syndrome. 42 The age range was 1 month old to 21 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 31 total studies, 15 studies evaluated drooling in children with cerebral palsy specifically or combination with an unspecified intellectual disability, 7 , 13 , 16 - 28 14 studies evaluated drooling in patients with a variety of neurologic or neurodevelopmental impairments, 10 , 14 , 29 - 40 1 study looked at hypersalivation in spinal muscle atrophy type I, 41 and 1 study involved a case series with Rett syndrome. 42 The age range was 1 month old to 21 years old.…”
Section: Resultsmentioning
confidence: 99%
“… 42 The total injection dose was weight-dependent in 8 studies, with children weighing <15 kg receiving 30 total units, 15 to 25 kg receiving 40 total units, and >25 kg receiving 50 total units, on average. 7 , 20 , 24 , 25 , 31 , 33 , 37 , 41 Bernardo et al 42 conducted the only study that used Xeomin ® for injections. The authors injected bilateral submandibular and parotid glands with a total dose of 150 units and found a statistically significant reduction in sialorrhea, with no adverse effects reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear aspiration studies can detect salivary aspiration but may not be able to differentiate between excessive salivation and an anatomical defect such as a laryngeal cleft 20 . Shoval et al described an unvalidated posterior drooling scale based on the presence or absence of coughing and choking while sitting or lying down 21 . For interpreting videofluoroscopic studies, the penetration‐aspiration scale is an 8‐point scale which can be used to interpret by characterizing depth and response to airway invasion.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Shoval et al described an unvalidated posterior drooling scale based on the presence or absence of coughing and choking while sitting or lying down. 21 For interpreting videofluoroscopic studies, the penetration‐aspiration scale is an 8‐point scale which can be used to interpret by characterizing depth and response to airway invasion. Borders and Brates performed a systematic review of the PAS literature in 2019 and found that studies using the PAS had poor interrater reliability and discrepancies in statistical treatment.…”
Section: Discussionmentioning
confidence: 99%